"We want the world and we want it now": Materialism, time perspectives and problem spending tendency of Chinese. (6th October 2016) - Ku, Lisbeth; Wu, Anise M. S.; Lao, Angie K. P.; Lam, Kerwin I. N.
Abstract : Chinese consumers' spending has been expanding rapidly in the past decade, and along with it household and credit card debt. The present research collected evidence to triangulate the contention that materialism is positively related with Chinese's problem spending tendency (PST), and that present‐time‐perspective (PTP) and future‐time perspectives (FTP) interact systematically with materialism to affect PST. A survey of the general population in Macao, China (Study 1; N = 239) confirmed that materialism was positively correlated with PST. An interaction between materialism and PTP intensified the relationship, whereas an interaction with FTP weakened the relationship. Another survey with a sample of university students (Study 2; N = 223) again found positive relationships among PST, materialism, and PTP, as measured by temporal discount rate. But further exploration showed that PST was only related with temporal discounting among high materialists, but not among low materialists. Study 3 experimentally examined the causal effects of materialism and FTP on PST. When being primed of an orientation towards materialism ( n = 33), the participants' planned consumption doubled that of the control group ( n = 31). A FTP prime interacted with materialism prime and put a "damper" on participants' planned spending ( n = 29), compared to their counterparts who were not primed of such a time perspective.